ERROR ANALYSIS OF USING AUXILIARY VERBS IN WRITING DESCRIPTIVE TEXT - Rony Arahta Sembiring; Agnes Shinta Marito Sibarani; Jeli Elvira Mangaraja (Journal of English Education and Teaching, 2021)
Grammar is complexity in learning English it makes many students often commit errors in learning. Making errors in writing is one of the processes for learning English .The aim of this research was to describe the students’ errors and its causes in using auxiliary verbs in the sentences. In this research, the writer limited the discussion on the error made by the students in using auxiliary verbs. The design of this research was quantitative approach in a form of descriptive analysis (percentage) that included observation, collecting the data the researcher used test as the instrument. The writer conducted the research to 31 students in first semester of English Literature in academic 2021/2022. The data were analyzed by using error analysis method. The error types were classified based on linguistic category, especially surface strategy taxonomy. The writer classified the types of error into omission, addition, misformation, and misordering. Among those four types, the most frequency error was misformation  that reached 102 errors or 61.44% . the other finding was the sources of error which are divided into three categories. Those are interlingual errors, intralingual errors, and communicative strategies. Communicative strategies errors is the most common source of error, there were 45.78%